2020
DOI: 10.1002/jctb.6505
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite biofilm aeration filter plays a pre‐nitritation role in autotrophic nitrogen removal from iron oxide red wastewater

Abstract: BACKGROUND: The completely autotrophic nitrogen removal over nitrite (CANON) system has excellent performance in treating ammonium-rich wastewater and it depends on ammonia oxidizing bacteria (AOB) working together with anammox bacteria in a reactor. Higher ammonium nitrogen loading requires higher aeration to provide sufficient dissolved oxygen (DO) for nitritation, whereas high-strength aeration in theCANON will destroy the sludge structure and inhibit the activity of anammox bacteria. The present study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…However, the characteristic peak of iron oxide crystalin in PZ/GL-SA-Urea microspheres did not appear. It could be concluded that the PZ­(Fe)/GL-SA-Urea microspheres were successfully prepared . As shown in Figure d, according to the three thermogravimetric curves of PZ, FeOOH, and PZ­(Fe), the stability of PZ was the highest, the stability of FeOOH was the lowest, and the stability of PZ­(Fe) was the middle, which indicated that the loading of FeOOH was successful.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…However, the characteristic peak of iron oxide crystalin in PZ/GL-SA-Urea microspheres did not appear. It could be concluded that the PZ­(Fe)/GL-SA-Urea microspheres were successfully prepared . As shown in Figure d, according to the three thermogravimetric curves of PZ, FeOOH, and PZ­(Fe), the stability of PZ was the highest, the stability of FeOOH was the lowest, and the stability of PZ­(Fe) was the middle, which indicated that the loading of FeOOH was successful.…”
Section: Resultsmentioning
confidence: 81%
“…It could be concluded that the PZ(Fe)/GL-SA-Urea microspheres were successfully prepared. 30 As shown in Figure 2d, according to the three thermogravimetric curves of PZ, FeOOH, and PZ(Fe), the stability of PZ was the highest, the stability of FeOOH was the lowest, and the stability of PZ(Fe) was the middle, which indicated that the loading of FeOOH was successful. The decrease of the curves was ascribed to the evaporation of water and the decomposition of organic matter on the surface at the initial stage of about 200 °C.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations